Levosimendan in Europe and China: An Appraisal of Evidence and Context - Xiangqing Kong (Radcliffe Medical Media, 2021)
The calcium sensitiser levosimendan (SIMDAX; Orion Pharma) has been in clinical use for the management of acute heart failure and a range of related syndromes in many countries around the world for two decades. More recently, levosimendan has become available in China. The authors have examined the profile of levosimendan in clinical trials conducted inside and outside China and grouped the findings under six headings: effects on haemodynamics, effects on natriuretic peptides, effect on symptoms of heart failure, renal effects, effect on survival, and safety profile. Their conclusions are that under each of these headings there are reasonable grounds to expect that the effects and clinical benefits established in trials and with wider clinical use in Europe and elsewhere will accrue also to Chinese patients. Therefore, the authors are confident that global experience with levosimendan provides a reliable guide to its optimal use and likely therapeutic effects in patients in China.